Optimization of Drying Temperature for Bintaro Fruit Seeds (Cerbera manghas) as a Bioinsecticide for Aedes aegypti Using a Tray Dryer - Fitria Gusfa; Alkausyari Aziz; Khayan; Taufik Anwar (Gema Lingkungan Kesehatan, 2024)
As a tropical country, Indonesia has various plants that can be utilized for human needs. One such plant is Bintaro (Cerbera manghas). Bintaro contains secondary metabolites that can be used as a bioinsecticide. These secondary metabolite compounds can degrade if dried at high temperatures. This study focused on optimizing the drying temperature of Bintaro fruit seeds (Cerbera manghas) using a tray dryer to produce bioinsecticide. The research employed a Completely Randomized Design (CRD) with four different drying temperature treatments: 40°C, 50°C, 60°C, and 70°C. The ethanol extracts from Bintaro seeds produced at each temperature treatment were tested for their effectiveness as a bio-insecticide against Aedes aegypti mosquitoes. The results indicated that the optimal drying temperature for Bintaro seeds, which provided the best bioinsecticide effectiveness, was 50°C.